The Fractured Legacy of Antitotalitarianism - Andrea Apollonio; Raffaele Alberto Ventura (De Europa)
This article, through a critical engagement with relevant literature, explores the genesis, the evolution and the political weaponisation of anti-totalitarianism in European politics. The first section situates the emergence of anti-totalitarianism within European academic and literary debates from the 1930s to the 1980s, framed around the master signifier of "totalitarianism." The second section examines its role in EU memory politics, particularly its adoption as a memory frame in response to the Eastern enlargement of the European Union (2004–2007), legitimising the EU as a democratic and human rights-based political community. The third section analyses the domestic instrumentalisation of EU anti-totalitarianism, with a focus on its use by the Italian post-fascist right to challenge the legacy of the Resistance and anti-fascism as a core element of Italy's civil religion. The article, while highlighting the unintended consequences of EU memory frames, concludes that the widespread invocation of totalitarianism has diluted the concept into a "floating signifier," undermining its historical meaning and political potency.